RETRACTED ARTICLE: Association of Life’s Essential 8 cardiovascular health with breast cancer incidence and mortality according to genetic susceptibility of breast cancer: a prospective cohort study - Yan Zhao; Yang Song; Xiangmin Li; Ayao Guo (Breast Cancer Research)
Abstract Background Accumulating evidence suggests that cardiovascular diseases and breast cancer share a number of common risk factors, however, evidence on the association between cardiovascular health (CVH) and breast cancer is limited. The present study aimed to assess the association of CVH, defined by Life’s Essential 8 (LE8) and genetic risk with breast cancer incidence and mortality among premenopausal and postmenopausal women. Methods We used data from the UK Biobank and conducted the multivariate Cox proportional-hazards models to examine associations of LE8 score and genetic risk with breast cancer incidence and mortality. Date on LE8 score was collected between 2006 and 2010 and composed of eight components, including behavioral metrics (diet, tobacco or nicotine exposure, physical activity, and sleep health), and biological metrics (body mass index, blood lipids, blood glucose, and blood pressure). The polygenic risk score (PRS) was calculated as the sum of effect sizes of individual genetic variants multiplied by the allele dosage. Results A total of 150,566 premenopausal and postmenopausal women were included. Compared to postmenopausal women with low LE8 score, those with high LE8 score were associated with 22% lower risk of breast cancer incidence (HR: 0.78, 95% CI: 0.70–0.87) and 43% lower risk of breast cancer mortality (HR: 0.57, 95% CI: 0.36–0.90). By contrast, we did not observe the significant association among premenopausal women. Further analyses stratified by PRS categories showed that high LE8 score was associated with 28% and 71% decreased risk of breast cancer incidence (HR: 0.72, 95% CI: 0.60–0.87) and mortality (HR: 0.29, 95% CI: 0.10–0.83) compared to low LE8 score among high genetic risk groups, but no significant associations were found among low genetic risk groups. Furthermore, compared with postmenopausal women with high LE8 score and low genetic risk, those with low LE8 score and high genetic risk were associated with increased risk of breast cancer incidence (HR: 6.26, 95% CI: 4.43–8.84). Conclusions The present study suggests that better CVH is a protective factor for both breast cancer incidence and mortality among postmenopausal women. Moreover, the risk of developing breast cancer caused by high genetic susceptibility could be largely offset by better CVH.